The Role of the Government and Civil Society in Political Stability after the 2024 Elections in Buleleng Regency - Syahrin, Alif Alfi; Idris, Muhammad; Adistanaya, I Made Bawadi; Putri, Kadek Dwi Cahyadianti; Cahyani, Kadek Candra Mahima (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
After the 2024 elections, attention will once again turn to the current state of political stability, particularly in Buleleng Regency. Therefore, the role of the government and civil society cannot be overlooked in maintaining political stability after the 2024 elections. The purpose of this study is to describe the implementation of the 2024 elections in Buleleng Regency, then describe the role of the government and civil society in maintaining political stability after the 2024 elections in Buleleng Regency, and describe the potential for projects to strengthen the profile of Pancasila students with the theme of the voice of democracy. The method used in this study is a qualitative approach with a case study. The results of the study reveal that the implementation of the 2024 elections in Buleleng Regency ran smoothly, with increased political participation and the involvement of civil society in educating the community. The role of the government and civil society in maintaining political stability after the 2024 elections in Buleleng Regency is to prevent identity politics, shape political awareness, and prevent practical politics. The potential for projects to strengthen the profile of Pancasila students on the theme of the voice of democracy by using various findings that can be used as a reference for schools in implementing P5 on the voice of democracy during the election of student council chairpersons and political education in schools.